Globalization, Religious Militancy Andterrorism in Southeast Asia Post-9f11: Implications For Regional Security (Journal of International Studies, 2020)
This paper attempts to underscore the significance of structural factors in the global political economy in providing explanatory value for the incidence/occurrence of religiously induced violence in several parts of the world including Southeast Asia. It argues that globalization unleashes forces and trends that aggravate the complexities of coping with modernity for large sectors of the world's citizenry who are also disempowered by this phenomenon. The crucial point however is that such structural disempowerment in itself is not the cause of religious militancy and terrorism. What makes the difference is the role of perception of such helplessness accompanied by a committed leader or ideologically-inclined groups who capitalize on this situation to further their own political agendas, by blaming it, via religious justification, on the West and secular forces aligned to it. In this way, the radical Islamists legitimize jihad (religiously induced violence) against the 'corrupt and immoral Western-led global order'. Additionally, internal failure in governance and religious reform to cope positively with the demands, challenges and opportunities presented by globalization, coupled with political manipulation by elites to either encourage or pre-empt religiously induced violence --is the second element of causation that is developed in this paper.